Effect of Axial Loading On the Lateral Behaviour of the Precast Post-Tensioned Segmental Column - Ahmad, Muhamad Arif (IRC, 2016)
Precast post-tensioned segmental columns were on the rise to satisfy the construction needs for the past years especially in bridge construction and in region with high seismic activity. The construction speed was reported to have been accelerated by 50% when precast. The purpose of this project is to study the effect of axial loading on lateral behaviour of precast post-tensioned segmental columns by modelling a 3D non-linear finite element model of the columns.